2006
DOI: 10.1016/j.cub.2006.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypically Linked Dichotomy in Sea Turtle Foraging Requires Multiple Conservation Approaches

Abstract: Marine turtles undergo dramatic ontogenic changes in body size and behavior, with the loggerhead sea turtle, Caretta caretta, typically switching from an initial oceanic juvenile stage to one in the neritic, where maturation is reached and breeding migrations are subsequently undertaken every 2-3 years [1-3]. Using satellite tracking, we investigated the migratory movements of adult females from one of the world's largest nesting aggregations at Cape Verde, West Africa. In direct contrast with the accepted lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
229
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 185 publications
(254 citation statements)
references
References 17 publications
15
229
1
6
Order By: Relevance
“…Mediterranean adult loggerheads do, however, exhibit some variety in their movements, with some turtles foraging in offshore oceanic waters for at least part of their inter-reproductive phase, sometimes keeping on the move without fixing to any specific site (Zbinden et al 2008;Luschi et al 2013;Schofield et al 2013). This pattern too is in general accordance with recent findings obtained elsewhere showing how loggerhead spatial behaviour is actually characterised by a considerable complexity (Hatase et al 2002;Hawkes et al 2006Hawkes et al , 2007Rees et al 2010). This variability is likely linked to the loggerhead's plastic and opportunistic foraging habits (McClellan et al 2010;Reich et al 2010;Narazaki et al 2013), which allow them to exploit both neritic and oceanic foraging grounds.…”
Section: General Considerationssupporting
confidence: 87%
See 2 more Smart Citations
“…Mediterranean adult loggerheads do, however, exhibit some variety in their movements, with some turtles foraging in offshore oceanic waters for at least part of their inter-reproductive phase, sometimes keeping on the move without fixing to any specific site (Zbinden et al 2008;Luschi et al 2013;Schofield et al 2013). This pattern too is in general accordance with recent findings obtained elsewhere showing how loggerhead spatial behaviour is actually characterised by a considerable complexity (Hatase et al 2002;Hawkes et al 2006Hawkes et al , 2007Rees et al 2010). This variability is likely linked to the loggerhead's plastic and opportunistic foraging habits (McClellan et al 2010;Reich et al 2010;Narazaki et al 2013), which allow them to exploit both neritic and oceanic foraging grounds.…”
Section: General Considerationssupporting
confidence: 87%
“…A degree of permanence in the same area was indicated by tag returns in the western and eastern Mediterranean (Casale et al 2007a), and was directly observed through satellite tracking in some cases in the western Mediterranean (Revelles et al 2007a) but not in others, either in the western (Cardona et al 2005;Eckert et al 2008;Cardona et al 2009) or in the eastern Mediterranean (Bentivegna 2002). In general, resident areas of juveniles in oceanic zones are much wider than in neritic zones (Revelles et al 2007b;Cardona et al 2009;Casale et al 2012aCasale et al , 2012b (Figure 4), as also observed for adults in the Mediterranean and elsewhere (Hawkes et al 2006;Schofield et al 2010a). Long-term residence of juveniles in neritic foraging grounds seems more common than in oceanic areas and it has been observed in various locations through tag returns (Casale et al 2007a;Revelles et al 2008) and satellite tracking Cardona et al 2009;Hochscheid et al 2010;Casale et al 2012aCasale et al , 2012bHochscheid et al 2013) (Figure 3).…”
Section: Large Juvenilessupporting
confidence: 63%
See 1 more Smart Citation
“…Other areas, linked to Cape Verde through migration and dispersal, are likely to be affected by these activities as well, underscoring the need to understand the connectivity of this rookery. These may include coastal areas from Mauritania to Sierra Leone, as well as the oceanic waters of Gambia, Guinea Konakry and Guinea Bissau, which satellite tracking studies have shown to constitute important feeding grounds for adult female loggerheads of Cape Verde (Hawkes et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This simple, rapid, non-invasive technique has the potential to advance our understanding of the enigmatic ecology of sea turtles. For example, although size-related differences in the use of feeding habitats (neritic vs. oceanic) by adult female loggerhead turtles have been reported within several populations (Hatase et al, 2002(Hatase et al, , 2007Hawkes et al, 2006), the mechanisms that produce and maintain this phenomenon are still unknown. Relative age information obtained with this method may become a key to help solve this phenomenon, which is closely related to facultative habitat shifts during ontogeny and alternative life histories in animals (Hatase et al, 2006;McClellan and Read, 2007).…”
mentioning
confidence: 99%